2018
DOI: 10.1002/jgm.3061
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length, ZNF208 genetic variants and risk of chronic obstructive pulmonary disease in the Hainan Li population

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a disease characterized by airflow limitation. It is not completely reversible and shows progressive development. ZNF208 rs8105767 affects telomere length, although the impact of telomere on COPD is still controversial. In the present study, we aimed to explore the impact of the ZNF208 gene polymorphism on telomere length and also that of telomere length on COPD in the Hainan Li population. Methods In total, 270 COPD patients and 288 controls were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Several studies have found that COPD patients have accelerated telomere shortening in leukocytes compared to regular smokers, and morbidity of the disease has been correlated to shorter telomere length [186,187,188]. When looking specifically at relative telomere length in airway epithelial cells from COPD patients, one study found no correlation of shorter telomere length with the disease.…”
Section: Inflammaging In Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…Several studies have found that COPD patients have accelerated telomere shortening in leukocytes compared to regular smokers, and morbidity of the disease has been correlated to shorter telomere length [186,187,188]. When looking specifically at relative telomere length in airway epithelial cells from COPD patients, one study found no correlation of shorter telomere length with the disease.…”
Section: Inflammaging In Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…Forty-one (41) were retained after the reading of titles and abstracts. Twenty-six (26) of these were excluded due to lacking eligibility criteria: eight studies were excluded as a result of statistically significant differences in age between COPD patients and controls [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]; three were excluded due to the investigation of biomarkers in lung or muscular tissue [ 30 , 31 , 32 ]; five studies had no control group [ 17 , 33 , 34 , 35 , 36 ]; three did not report the results of statistical testing for discrepancies in age between COPD patients and controls [ 37 , 38 , 39 ]; and one did not perform comparisons [ 40 ]. Two articles employed a study design that was inconsistent with the stated eligibility criteria [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…These ZFPs have the potential to be used in the development of a predictive gene signature, which could have prognostic value in relation to ovarian cancer and its response to PARP inhibitors. The sources cited for this information are [54,62,[63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%